2023
DOI: 10.1111/hojo.12535
|View full text |Cite
|
Sign up to set email alerts
|

Unsubstantiated use of force in the killing of Atatiana Jefferson: A critical policy analysis

Latocia Keyes,
Vance D. Keyes,
Raymond Adams
et al.

Abstract: A sustained history of white supremacy is in the system of policing. Police engage in state‐sanctioned murders of African American women. Too many times, police state‐sanctioned violence is disregarded. A critical analysis and applicable theoretical frameworks were used to examine the Fort Worth Police Department's (FWPD's) Use of Force Policy in the case of Atatiana Jefferson's murder. The findings show cultural situatedness impacted this case. In other words, the normed cultural, social and environmental fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…Oversight offers alternatives to traditional police accountability and may be more amenable to citizens' grievances based on excessive force (Task Force on Policing, 2021). Excessive force by municipal police includes George Floyd, killed in Minneapolis, MN; Atatiana Jefferson in Fort Worth, TX; and Tyre Nichols in Memphis, TN, are examples of why oversight is pursued (Jackson et al, 2023;Keyes et al, 2023;Schweikert, 2023). According to De Angelis et al (2016), 97 public oversight boards indicated that about 80% of those boards were developed due to police use of excessive force and police treating marginalized communities as criminogenic based on racialization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oversight offers alternatives to traditional police accountability and may be more amenable to citizens' grievances based on excessive force (Task Force on Policing, 2021). Excessive force by municipal police includes George Floyd, killed in Minneapolis, MN; Atatiana Jefferson in Fort Worth, TX; and Tyre Nichols in Memphis, TN, are examples of why oversight is pursued (Jackson et al, 2023;Keyes et al, 2023;Schweikert, 2023). According to De Angelis et al (2016), 97 public oversight boards indicated that about 80% of those boards were developed due to police use of excessive force and police treating marginalized communities as criminogenic based on racialization.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive force by municipal police includes George Floyd, killed in Minneapolis, MN; Atatiana Jefferson in Fort Worth, TX; and Tyre Nichols in Memphis, TN, are examples of why oversight is pursued (Jackson et al. , 2023; Keyes et al. , 2023; Schweikert, 2023).…”
Section: Introductionmentioning
confidence: 99%